Reporting of hyperprolactinaemia post-polyethylene glycol (PEG) precipitation at Hospital Tengku Ampuan Rahimah Klang, Malaysia - Zaharudin, Mohd Radzli; Samsudin, Intan Nureslyna; Abdul Hamid, Hanisah; C. Thambiah, Subashini (Universiti Putra Malaysia, 2024)
Introduction: Macroprolactinaemia is defined as hyperprolactinaemia due to excess macroprolactin in the presence of normal monomeric prolactin. Failure to identify macroprolactinaemia may result in patients being subjected to unnecessary investigations and inappropriate treatment for hyperprolactinaemia. In our centre, screening for macroprolactinaemia is currently performed at the request of the treating physician. The study thus aimed to determine the frequency of macroprolactinaemia in samples with serum prolactin ≥700 mIU/L in Hospital Tengku Ampuan Rahimah (HTAR) and to determine the presence of true hyperprolactinaemia in these cases. Methods: A cross-sectional study among hyperprolactinaemic subjects in HTAR, using serum specimens received by the laboratory for measurement of prolactin between October 2018 and September 2019. Samples with prolactin ≥700 mIU/L were screened for macroprolactinaemia using the polyethylene glycol (PEG) precipitation technique. Macroprolactinaemia was present when the percentage recovery of prolactin post-PEG was <40%. Assay-specific post-PEG monomeric prolactin levels were also reported, with levels above the upper limit of reference intervals indicated the presence of true hyperprolactinaemia. Results: A total of 101 samples were subjected to PEG precipitation. Macroprolactinaemia was found in four (4%) samples, whilst eight (7.9%) were categorised as indeterminate (percentage recovery of 40-60%). The remaining 89 (88.1%) samples had a percentage recovery >60%, hence considered negative for macroprolactinaemia. All four samples with macroprolactinaemia also had raised monomeric prolactin levels indicating the co-existence of macroprolactinaemia in subjects with true hyperprolactinaemia. Similarly, in the indeterminate group, all eight had raised monomeric prolactin levels. Conclusion: In one-year period in HTAR, macroprolactinaemia was detected in 4% of subjects with prolactin ≥700 mIU/L, all of whom also had raised monomeric prolactin levels. The common occurrence of both macroprolactinaemia and true hyperprolactinaemia warrants the reporting of both percentage recovery and monomeric prolactin levels post-PEG.